Virulence of Five Root-Knot Nematodes (Meloidogyne spp.) on Nine Industrial Hemp (Cannabis sativa L.) Varieties and Nematicidal Potential of Hemp Seed Extracts Against Meloidogyne javanica - Dionysios Ntinokas; Ioannis Roussis; Antonios Mavroeidis; Panteleimon Stavropoulos; Antigolena Folina; Ioanna Kakabouki; Emmanuel A. Tzortzakakis; Dimitrios Bilalis; Ioannis O. Giannakou (Plants)
The most common and damaging plant parasitic nematodes are root-knot nematodes (RNK). Although hemp has been clearly infected by RNK, little information is available regarding the extent of the damage and losses caused. In addition, no information is available concerning hemp seed extracts’ activity against RNK. In the current research, a greenhouse experiment was developed to evaluate the infection effect of five RKN species (Meloidogyne javanica, M. incognita, M. arenaria, M. hapla, and M. luci) in nine industrial hemp varieties (Fedora 17, Ferimon 12, Futura 75, Santhica 27, Santhica 70, KC Dora, KC Zuzana, Zenit, and USO 31), as was a laboratory experiment to evaluate the nematicidal activity of aqueous and water extracts of hemp seeds against second-stage juveniles (J2s) of M. javanica. The results revealed that the five evaluated Meloidogyne species were pathogenic to hemp plants. The lowest shoot weights were recorded in plants that were inoculated with M. javanica and M. luci (4.65 and 4.53 g, respectively). As for the root system, the most severe damage of the roots was detected in M. incognita-infected plants, presenting the lowest root weight (1.72 g). Regarding hemp varieties, the most susceptible were USO 31, Fedora 17, Ferimon 12, and Zenit, while Futura 75 hosted the lowest nematode numbers, including the lowest values of females per gram of root (10.66), number of egg masses per gram of root (4.70), and fecundity (33.68 eggs per egg mass). Moreover, this research showed that aqueous and ethanolic hemp seed extracts can control M. javanica. After 24, 48, 72, and 96 h of exposure to high concentrations (250–2000 ppm) of ethanolic and aqueous extracts, the J2s were permanently paralyzed; however, at low concentrations, only the ethanolic extract was effective. The ethanolic extract paralyzed J2s at concentrations higher than 62.5 ppm and reduced the egg hatching by up to 76% compared to the control treatment. In general, the efficacy of the aqueous extract was considerably lower than that of the ethanolic extract.